(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article explores the operations of the Department of Land and State Property established in Turkestan in 1897, with particular emphasis on its activities within Samarkand region. The study provides a detailed examination of the structure and distribution of land plots, the specific characteristics of local agricultural practices, the development of irrigation systems, and the institutional measures implemented to manage the region’s agrarian potential. Drawing upon archival documents and statistical data, the author highlights both the achievements and the persistent challenges in this domain.